(untitled) (Al-Farooq Journal of Sciences, 2026)
The goal of this study was to assess how tourism marketing impacts the ability of tourism agencies in Tripoli to gain a competitive advantage. The study treated tourism marketing as the independent variable and achieving competitive advantage as the dependent variable. A sample size of 107 respondents was targeted using a simple random sampling method. Data was collected through a questionnaire, with 98 valid responses analyzed using SPSS after eliminating 9 incomplete responses. The study used a descriptive-analytical approach to examine the relationship between its variables. The findings showed that the agency had successfully built lasting and strong relationships with clients by maintaining honesty, fulfilling promises, and demonstrating professionalism in all interactions